2013
DOI: 10.1016/j.celrep.2013.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine-Therapy-Resistant ESR1 Variants Revealed by Genomic Characterization of Breast-Cancer-Derived Xenografts

Abstract: SUMMARY To characterize patient-derived xenografts (PDXs) for functional studies, we made whole-genome comparisons with originating breast cancers representative of the major intrinsic subtypes. Structural and copy number aberrations were found to be retained with high fidelity. However, at the single-nucleotide level, variable numbers of PDX-specific somatic events were documented, although they were only rarely functionally significant. Variant allele frequencies were often preserved in the PDXs, demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
631
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(665 citation statements)
references
References 52 publications
27
631
5
2
Order By: Relevance
“…This finding is consistent with the known concept of tumor heterogeneity within a primary tumor and metastatic sites (25). These findings are also in accord with recent data demonstrating that acquired ER mutations can be found in liver metastatic lesions, but not pulmonary metastases within the same patient (15), and additional studies revealing that ER mutations are relatively rare in primary breast cancers but are more common after acquired resistance to endocrine therapies (12)(13)(14)16). Gene expression qRT-PCR data from the prior analysis in Fig. 1B correlated with IHC results for the metastatic sites queried in these five patients.…”
Section: Macrod2 Is Amplified In a Subset Of Tamoxifen-resistant Breastsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with the known concept of tumor heterogeneity within a primary tumor and metastatic sites (25). These findings are also in accord with recent data demonstrating that acquired ER mutations can be found in liver metastatic lesions, but not pulmonary metastases within the same patient (15), and additional studies revealing that ER mutations are relatively rare in primary breast cancers but are more common after acquired resistance to endocrine therapies (12)(13)(14)16). Gene expression qRT-PCR data from the prior analysis in Fig. 1B correlated with IHC results for the metastatic sites queried in these five patients.…”
Section: Macrod2 Is Amplified In a Subset Of Tamoxifen-resistant Breastsupporting
confidence: 91%
“…In part, this is due to the heterogeneous nature of breast cancers, resulting in multiple mechanisms of resistance. For example, past studies have demonstrated that tamoxifen resistance is mediated by differential expression of nuclear hormone receptor coregulators (2, 3), growth factor signaling crosstalk (4-7), regulation of microRNAs (8), cyclin dependent kinases (CKDs) (9), CDK inhibitors (10,11), and more recently, acquired somatic mutations and alterations in ER (12)(13)(14)(15)(16)(17). Further insight into the molecular mediators of tamoxifen and hormone therapy resistance would have great impact on the ability to target genes and pathways that could overcome drug resistance and lead to improved clinical outcomes.…”
mentioning
confidence: 99%
“…Furthermore, polyclonal sub-structure may emerge even in xenografts that have undergone a modest population bottleneck on initial engraftment. These dynamic processes are not evident from histopathological or imaging characteristics, which remain broadly stable, consistent with previous reports 8,9,23 .…”
supporting
confidence: 91%
“…Expansion of minor subclones has been suggested in previous xenotransplantation studies using malignant epithelial 10,[21][22][23] or hematopoietic 24,25 cells, without formal resolution of the clonal genotypes or pattern of subsequent clonal dynamics. In contrast with preliminary studies of xenoengraftment, we find correlated dynamics of clones defined by SNVs or copy number aberrations as clonal marks.…”
mentioning
confidence: 99%
“…Conversely, not all patients with complete reduction in ER availability will experience clinical benefi t, because other mechanisms aside from inadequate dosing can be responsible for therapy failure. Among these potential mechanisms are ESR1 mutation and upregulation of growth factor receptor pathways ( 24 ).…”
Section: Discussionmentioning
confidence: 99%